Performa dan Profil Darah Kambing Boerka yang Diberi Ransum Mengandung Frass Pod Kakao dan Frass Bungkil Inti Sawit: Performance and Blood Profile of Boerka Goats Fed Ration Containing Cocoa-pod Frass and Palm Kernel Meal Frass - nabawi, Soviro Nurul Lisa; Fitriana, Eko Lela; Astuti, Dewi Apri; Tarigan, Andi (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This study was aimed at evaluating the utilization of total mixed rations containing cocoa pod frass and palm kernel meal frass from BSF larvae on the performance and blood profile of boerka goats. Twelve male boerka goats with an average initial weight of 23,79±3,49 kg were used in this experiment, which were then grouped into four groups based on body weight. The treatment consisted of R0: control ration (30% forage+70% concentrate), R1: ration containing 15% cocoa pod frass+15% forage+70% concentrate, and R2: 15% palm kernel meal frass+15% forage+70% concentrate. The observed parameters were nutrient consumption, body weight gain, feed efficiency, haematological profile and blood metabolites. The study used a randomized block design and the collected data would be analysed using analysis of variance as the significance of treatments was continued with Duncan test. The result showed that ration containing cocoa pod frass gave a better response to the performance and blood profile of goats. The conclusion of this study was the feeding ration containing cocoa pod frass and palm kernel meal frass could be used as a mixture in goat rations and did not interfere with the goat’s health. Key words: blood profile, boerka, frass of black soldier fly, performance